Grey literature, koleksi yang terlupakan pada perpustakaan utama UIN Syarif Hidayatullah Jakarta: Lemahnya penerapan local intellectual deposit - Pungki Purnomo (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2007)
The aim of this article is to discuss the involvement of UIN Syarif Hidayatullah Jakarta community in developing the dynamic intellectual in this globalization era with the role of the main library in acquiring, storing, and disseminating the local university intellectual wealth to the end user in a fast, timely and efficient way. Inevitably, that UIN Jakarta and its structural and non-structural organizations have reliable potential to participate in development of the knowledge production in national, region and global level. Unfortunately, our institution has very weak tradition in documenting the intellectual wealth produced by UIN Jakarta local community. Although the responsibility of the intellectual wealth preservation in UIN Jakarta must involve all university units and organizations, yet, the role of the main library must be more active and dynamic than the other UIN Jakarta units and organizations. This article is based on the research project conducted by the writer in 2007. There are at least three issues discussed in this article. The first issue discusses the introduction of general concept on grey literatures and its development, role and function in educational institutions. The second issue discusses the contribution of UIN Jakarta organizations (both structural and non-structural) in development of grey literature collection. Finally it discusses some barriers faced by the UIN Jakarta main library in preserving, especially, the local UIN Jakarta intellectual wealth. As a conclusion of this article discussed some suggestions for improvement of the intellectual deposit program coordinated by the UIN Jakarta main library. Key words: Intellectual deposit program, Grey Literature, local intellectual wealth.